Dexamethasone improves therapeutic outcomes in a preclinical bacterial epididymitis mouse model. Issue 7 (18th June 2019) - Klein, Britta; Pant, Swapnila; Bhushan, Sudhanshu; Kautz, Julia; Rudat, Carsten; Kispert, Andreas; Pilatz, Adrian; Wijayarathna, Rukmali; Middendorff, Ralf; Loveland, Kate L; Hedger, Mark P; Meinhardt, Andreas
Abstract: STUDY QUESTION: Can dexamethasone improve infertility-related cauda epididymidal tissue damage caused by bacterial epididymitis? SUMMARY ANSWER: Dexamethasone in addition to anti-microbial treatment effectively reduces long-term deleterious epididymal tissue damage by dampening the host's adaptive immune response. WHAT IS KNOWN ALREADY: Despite effective anti-microbial treatment, ~40% of patients with epididymitis experience subsequent sub- or infertility. An epididymitis mouse model has shown that the host immune response is mainly responsible for the magnitude of epididymal tissue damage that is fundamentally causative of the subsequent fertility issues. STUDY DESIGN, SIZE, DURATION: Bacterial epididymitis was induced in male mice by using uropathogenic Escherichia coli (UPEC). From Day 3 after infection onwards, mice were treated with daily doses of levofloxacin (20 mg/kg, total n  = 12 mice), dexamethasone (0.5 mg/kg, total n  = 9) or both in combination (total n  = 11) for seven consecutive days. Control animals were left untreated, i.e. given no interventional treatment following UPEC infection (total n  = 11). Half of the animals from each group were killed either at 10 or 31 days post-infection. PARTICIPANTS/MATERIALS, SETTING, METHODS: A mouse model of induced bacterial epididymitis was applied to adult male C57BL/6J mice. At the respective endpoints (10 or 31 days post-infection), epididymides were collected. Effectiveness of antibiotic treatment was assessed by plating of epididymal homogenates onto lysogeny broth agar plates. Overall tissue morphology and the degree and nature of tissue damage were assessed histologically. Quantitative RT-PCR was used to assess local cytokine transcript levels. Blood was drawn and serum analysed for systemic IgG and IgM levels by ELISA. In addition, correlation analyses of clinical data and serum-analyses of IgG and IgM levels in patients with epididymitis were performed. MAIN RESULTS AND THE ROLE OF CHANCE: The addition of dexamethasone to the standard anti-microbial treatment did not further worsen epididymal tissue integrity. In fact, an obviously dampened immune response and reduced tissue reaction/damage was observed at both 10 and 31 days post-infection following combined treatment. More specifically, epididymal duct continuity was preserved, enabling sperm transit. In contrast, in untreated or antibiotic-treated animals, damage of the epididymal duct and duct constrictions were observed, associated with a lack of cauda spermatozoa. In line with the bacteriostatic/bactericidal effect of levofloxacin (alone as well as in combination), local cytokine transcript levels were significantly and similarly reduced in animals treated with levofloxacin alone ( P  < 0.01) or in combination with dexamethasone ( P  < 0.05) compared to UPEC-infected untreated animals. Interestingly, the addition of dexamethasone to the anti-microbial treatment induced a unique dampening effect on adaptive immunity, since systemic IgG and IgM levels as well as the pan-T cell marker CD3 were reduced at both 10 and 31 days post-infection. LIMITATIONS, REASONS FOR CAUTION: Breeding studies to address the fertility-protecting effect of the combined treatment were not possible in the experimental animals because the vas deferens was ligated (model specific). WIDER IMPLICATIONS OF THE FINDINGS: Whereas innate immunity is necessary and involved in acute bacterial clearance, adaptive immunity seems to be responsible for long-term, subclinical immunological activities that may negatively affect the pathogenesis of bacterial epididymitis even after effective bacterial eradication. These effects can be reduced in mice by the additional treatment with dexamethasone. This immunological characteristic of bacterial epididymitis shows similarities to the Jarisch–Herxheimer reaction known from other types of bacterial infection. STUDY FUNDING/COMPETING INTEREST(S): The study was supported by grants from the Deutsche Forschungsgemeinschaft, Monash University and the Medical Faculty of Justus-Liebig University to the International Research Training Group on 'Molecular pathogenesis of male reproductive disorders' (GRK 1871). R.W., K.L.L. and M.P.H. were supported by grants from the National Health and Medical Research Council of Australia (ID1079646, ID1081987, ID1020269 and ID1063843) and by the Victorian Government's Operational Infrastructure Support Program. The authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: No clinical trial involved.